Heat exchanger and method for manufacturing heat exchanger

CN119156511APending Publication Date: 2024-12-17RESONAC CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380038503.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-23
Filing Date
2023-11-15
Publication Date
2024-12-17

Smart Images

  • Figure CN119156511A_ABST
    Figure CN119156511A_ABST
Patent Text Reader

Abstract

Provided is a method for manufacturing a heat exchanger capable of further improving productivity, and more specifically, the method has a short bonding process time and a long opening time. This method for manufacturing a heat exchanger comprises: a pre-bonding step for preparing a laminate in a state in which a surface sheet (3), a solid adhesive (28), which is mainly composed of at least one amorphous thermoplastic resin selected from the group consisting of thermoplastic epoxy resins and phenoxy resins, and a flow path-forming sheet (4), which is mainly composed of at least one amorphous thermoplastic resin selected from the group consisting of thermoplastic epoxy resins and phenoxy resins, are arranged in this order, and a bonding step for bonding the surface sheet (3), the solid adhesive (28), and the flow path-forming sheet (4); the flow path forming sheet (4) has a flow path (20) on a surface (30) facing the surface sheet (3), and the surface sheet (3) and the flow path forming sheet (4) are joined together by heating and pressurizing the laminate to melt the solid adhesive. The epoxy equivalent of the amorphous thermoplastic resin is 1,600 or more, or the amorphous thermoplastic resin does not contain an epoxy group, and the heat of fusion of the amorphous thermoplastic resin is 15 J / g or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a heat exchanger and a method of manufacturing the heat exchanger. Background Art

[0002] In battery modules installed in electric vehicles or hybrid vehicles, large amounts of heat are generated by the battery pack due to continuous large-capacity charging or discharging. Therefore, a technology has been proposed to avoid adverse effects of heat by incorporating a water-cooled cooler or a heat pipe in the battery module.

[0003] For example, Patent Document 1 discloses a heat exchanger in which two or more etched metal sheets are stacked to form a container in which at least a part of the outer periphery is sealed by bonding.

[0004] Prior Art Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2015-059693 Summary of the invention

[0006] Problems to be solved by the invention

[0007] The heat exchanger of Patent Document 1 mentioned above has a problem that the core forming the outer peripheral wall and the flow path is sealed by diffusion bonding, which is difficult and it is difficult to improve the production efficiency.

[0008] In the present disclosure, the bonding process time refers to the time from the initial contact of the bonding agent with one or both substrates constituting the bonded body to the completion of the production of the bonded body. For example, the bonding process time includes the time required for the coating process and drying process of the liquid bonding agent or the loading process of the solid bonding agent, and the time required for bonding the substrates to each other (for example, curing the bonding layer). The shorter the bonding process time, the more the productivity of the bonded body can be improved.

[0009] In the present disclosure, the open time refers to the time limit from coating or placing the bonding agent on one substrate (e.g., the first component) to the completion of placing the other substrate (e.g., the second component). If the open time is within the open time, the bonding force of the bonding agent will not decrease, and the substrates can be bonded with sufficient bonding force. The longer the open time, the more freedom of the manufacturing process of the bonded body can be increased.

[0010] The present invention aims to provide a method for manufacturing a heat exchanger, which can further improve productivity, more specifically, shorten the joining process time and lengthen the open time. In addition, the present invention aims to provide a heat exchanger in which components are joined with high joining strength.

[0011] Means for solving problems

[0012] The present disclosure includes the following technical solutions.

[0013] [1] A method for manufacturing a heat exchanger, comprising a pre-joining step and a joining step,

[0014] In the pre-bonding step, a laminated body is prepared in which a surface sheet, a solid bonding agent, and a flow path forming sheet are sequentially arranged, the solid bonding agent mainly comprising at least one amorphous thermoplastic resin selected from thermoplastic epoxy resins and phenoxy resins, and the flow path forming sheet has a flow path on a surface opposite to the surface sheet.

[0015] In the bonding step, the laminate is heated and pressurized to melt the solid bonding agent, thereby bonding the surface sheet and the flow path forming sheet.

[0016] The epoxy equivalent of the amorphous thermoplastic resin is 1,600 or more, or the amorphous thermoplastic resin does not contain an epoxy group, and the heat of fusion of the amorphous thermoplastic resin is 15 J / g or less.

[0017] [2] The method for manufacturing a heat exchanger according to [1], wherein the heating and pressurizing are performed under the conditions of 100° C. to 400° C. and 0.01 MPa to 20 MPa.

[0018] [3] The method for manufacturing a heat exchanger according to [1] or [2], wherein the solid bonding agent before melting has any one shape selected from the group consisting of a film, a rod, particles, and a powder.

[0019] [4] The method for manufacturing a heat exchanger according to any one of [1] to [3], wherein the surface sheet and the flow path forming sheet are made of metal.

[0020] [5] A heat exchanger comprising a surface sheet, a flow path forming sheet, and an adhesive layer for bonding the surface sheet to the flow path forming sheet, wherein the adhesive layer comprises a solid adhesive having at least one amorphous thermoplastic resin selected from thermoplastic epoxy resins and phenoxy resins as a main component, the epoxy equivalent of the amorphous thermoplastic resin being greater than 1,600, or the amorphous thermoplastic resin being free of epoxy groups, and the heat of fusion of the amorphous thermoplastic resin being less than 15 J / g.

[0021] [6] The heat exchanger according to [5], wherein the surface sheet and the flow path forming sheet are made of metal.

[0022] [7] The heat exchanger according to [5] or [6],

[0023] The surface sheet has an inlet and an outlet,

[0024] The flow path forming sheet has a flow path on a surface opposite to the surface sheet.

[0025] The flow path includes: an inlet corresponding portion connected to the inlet, an outlet corresponding portion connected to the outlet, and a plurality of intersections extending in a direction intersecting a direction connecting the inlet corresponding portion and the outlet corresponding portion.

[0026] The surface sheet and the flow path forming sheet are joined to each other by welding so as to surround the outside of the flow path.

[0027] The adhesive layer is provided at least at one location along the plurality of intersections.

[0028] [8] The heat exchanger according to [7],

[0029] The surface sheet comprises a first surface sheet and a second surface sheet,

[0030] The flow path penetrates the flow path forming sheet in the thickness direction,

[0031] The first surface sheet, the flow path forming sheet and the second surface sheet are sequentially provided in the thickness direction.

[0032] The first surface sheet is provided with the inlet and the outlet.

[0033] [9] The heat exchanger according to [7],

[0034] The surface sheet comprises a first surface sheet and a second surface sheet,

[0035] The flow path penetrates the flow path forming sheet in the thickness direction,

[0036] The first surface sheet, the flow path forming sheet and the second surface sheet are sequentially provided in the thickness direction.

[0037] The first surface sheet is provided with the inlet, and the second surface sheet is provided with the outlet.

[0038] Effects of the Invention

[0039] According to the method for manufacturing a heat exchanger disclosed herein, the productivity of the heat exchanger can be further improved. More specifically, the heat exchanger can be manufactured with a short joining process time and a long open time, and the constituent parts can be joined with high joining strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a perspective view of a heat exchanger according to one embodiment.

[0041] Figure 2This is an exploded perspective view of a heat exchanger according to one embodiment.

[0042] Figure 3 This is a top view of a flow channel forming sheet provided with a solid bonding agent.

[0043] Figure 4 It is a top view of the heat exchanger according to Modification 1.

[0044] Figure 5 It is an exploded perspective view of a heat exchanger according to Modification 2.

[0045] Figure 6 It is a schematic cross-sectional view showing a state where a first member and a second member are bonded together via an adhesive layer containing a solid bonding agent. DETAILED DESCRIPTION

[0046] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the drawings. The present disclosure is not limited to the following embodiments, and various modifications can be made within the scope of the gist of the invention.

[0047] In the following description, the X direction, Y direction, and Z direction of the rectangular coordinate system are defined as follows. The Z direction (third direction) is the thickness direction of the heat exchanger. The X direction (first direction) and the Y direction (second direction) are the surface directions of the heat exchanger, and are the length direction and the width direction when the top view shape of the heat exchanger is a rectangle.

[0048] “Along” a certain reference includes along a direction within a range of less than ±45° relative to a certain reference. The end of a certain direction of a certain component, etc., refers to the range from the end edge of the component in that direction to a length less than 1 / 5 (preferably 1 / 10) of the overall length of the component, etc. in that direction.

[0049] In the present disclosure, joining refers to connecting objects to each other, and bonding and welding are subordinate concepts. Bonding refers to the joining of two bonded materials (materials to be bonded) by organic materials (curable resins, thermoplastic resins, etc.) such as tapes and adhesives. Welding refers to the joining by utilizing mutual entanglement and crystallization caused by molecular diffusion during the process of melting the surface of thermoplastic resins, etc., contact pressurization, and cooling, or by molecular interaction with the substrate during melting.

[0050] [Heat exchanger]

[0051] Figure 1The heat exchanger 1 of one embodiment shown is a rectangular plate-shaped member having a plane parallel to the X direction and the Y direction orthogonal to the Z direction (hereinafter also referred to as the "XY plane"), and includes a surface sheet 3, a flow path forming sheet 4, and an adhesive layer (not shown in this figure) that joins the surface sheet 3 and the flow path forming sheet 4. In the following description, the heat exchanger is sometimes referred to as a "joined body", the surface sheet is referred to as a "first member", and the flow path forming sheet is referred to as a "second member".

[0052] In the case of this embodiment, the heat exchanger 1 includes a first surface sheet 10 as a surface sheet 3, an intermediate sheet 12 as a flow path forming sheet 4, and a second surface sheet 14. The first surface sheet 10, the intermediate sheet 12, and the second surface sheet 14 are arranged in this order along the Z direction, and the relative surfaces are bonded to each other by an adhesive layer. Figure 1 The heat exchanger 1 shown is a rectangular plate-shaped member having an X direction as its long side direction and a Y direction as its short side direction.

[0053] like Figure 2 As shown, the first surface sheet 10 can use a plate-like member with a thickness of 0.5 mm to 3 mm, and has an inlet 16 and an outlet 18 that penetrate in the Z direction. The inlet 16 and the outlet 18 are formed at positions separated from each other along the X direction. That is, the inlet 16 is formed at the end of one side of the first surface sheet 10 in the X direction, and the outlet 18 is formed at the end of the other side of the first surface sheet 10 in the X direction. The material of the first surface sheet 10 is metal or resin, preferably metal.

[0054] The intermediate sheet 12 may use a plate-like member having a thickness of 1.0 mm to 5 mm, and has a flow path 20. The flow path 20 is a groove having a predetermined width. The flow path 20 penetrates the intermediate sheet 12 in the Z direction. The flow path 20 has an inlet corresponding portion 22 and an outlet corresponding portion 24. The inlet corresponding portion 22 is arranged at an end portion on one side of the intermediate sheet 12 in the X direction, and the outlet corresponding portion 24 is arranged at an end portion on the other side of the intermediate sheet 12 in the X direction. The inlet corresponding portion 22 is formed at a position corresponding to the inlet 16 of the first surface sheet 10, and the outlet corresponding portion 24 is formed at a position corresponding to the outlet 18 of the first surface sheet 10.

[0055] The flow path 20 has a plurality of intersections 26 extending in a direction intersecting the direction connecting the inlet corresponding portion 22 and the outlet corresponding portion 24. In the case of the present embodiment, the direction connecting the inlet corresponding portion 22 and the outlet corresponding portion 24 is parallel to the X direction. The flow path 20 has a plurality of ( Figure 1In the case of the flow passage 20, there are 6) cross passages 26. The plurality of cross passages 26 are arranged at predetermined intervals in the X direction. The flow passage 20 is a zigzag shape that is alternately bent to both sides of the Y direction between the inlet corresponding portion 22 and the outlet corresponding portion 24. One side of the flow passage 20 in the Z direction is closed by the first surface sheet 10, and the other side in the Z direction is closed by the second surface sheet side 14. In this way, the flow passage 20 is formed to be able to flow refrigerant from the inlet corresponding portion 22 to the outlet corresponding portion 24 (not shown). The material of the intermediate sheet 12 is metal or resin, preferably metal. The intermediate sheet 12 can be the same material as the first surface sheet 10, or a different material.

[0056] The second surface sheet 14 may be a plate-shaped member having a thickness of 0.5 mm to 3 mm, and may be made of the same material as the first surface sheet 10 and the intermediate sheet 12 or a different material.

[0057] The above-mentioned metal is preferably at least one selected from aluminum, iron, copper, magnesium and their alloys. From the viewpoint of the bonding strength and the strength of the substrate and the strength of the interfacial bonding strength with the above-mentioned solid bonding agent, it is more preferably at least one selected from aluminum, aluminum alloys and iron alloys, and further preferably at least one selected from aluminum and aluminum alloys having excellent heat dissipation efficiency.

[0058] The resin is preferably one selected from the group consisting of a thermoplastic resin, a thermosetting resin, and a fiber reinforced plastic (FRP), and a thermoplastic resin is more preferred from the viewpoints of adhesive strength, cost, and ease of molding.

[0059] By forming sheet 4 or both of surface sheet 3 or flow path into suitable pre-treatment respectively, high bonding strength can be obtained. As pre-treatment, preferably the pre-treatment of cleaning substrate surface or the pre-treatment of giving concavoconvex to the surface. Pre-treatment can only be implemented 1 kind, also can implement more than 2 kinds. As the concrete method of these pre-treatments, known method can be used.

[0060] Specifically, when the material of the above-mentioned component is aluminum, glass, ceramic or iron, it is preferably selected from at least one of degreasing treatment, UV ozone treatment, sandblasting, grinding treatment, plasma treatment and etching treatment. When the material of the above-mentioned component is FRP, polypropylene, polycarbonate, polymethyl methacrylate, polyetherimide, polyamide or polybutylene terephthalate, it is preferably selected from at least one of degreasing treatment, UV ozone treatment, sandblasting, grinding treatment, plasma treatment and corona discharge treatment.

[0061] A heat exchanger 1 according to one embodiment can be manufactured by a manufacturing method including a pre-joining process and a joining process. In the pre-joining process, a laminated body is prepared in which a surface sheet 3, a solid bonding agent, and a flow path forming sheet 4 are sequentially arranged. In the case of this embodiment, the laminated body is sequentially arranged with a first surface sheet 10, a solid bonding agent, an intermediate sheet 12, a solid bonding agent, and a second surface sheet 14.

[0062] like Figure 3 As shown, the solid adhesive 28 is in a strip shape and is arranged along the intersection 26. The solid adhesive 28 is arranged on the first surface 30 of the intermediate sheet 12 opposite to the first surface sheet 10 and the second surface 32 opposite to the second surface sheet 14. Since the positions where the solid adhesive 28 is arranged are the same on the first surface 30 and the second surface 32, only the first surface 30 will be described.

[0063] Figure 3 The solid adhesive 28 shown has a first solid adhesive 34 and a second solid adhesive 36. The first solid adhesive 34 extends along the intersection 26 and is disposed between adjacent intersections 26. The second solid adhesive 36 extends along the X direction and is disposed at a position outside the flow path 20 relative to the respective terminals of the inlet corresponding portion 22 and the outlet corresponding portion 24. The solid adhesive 28 is disposed at a position inside the XY plane relative to the outer peripheral portion surrounding the outer side of the flow path 20. The outer peripheral portion has a predetermined width from the outer edge of the intermediate sheet 12 to the inner side of the XY plane. The outer edge of the outer peripheral portion is the outer edge of the intermediate sheet 12, and the inner edge of the outer peripheral portion is outside the XY plane relative to the outer edge of the flow path 20.

[0064] In the bonding process, the stacked body is heated and pressurized under predetermined conditions to melt the solid bonding agent 28. Then, the solid bonding agent 28 is solidified by lowering the temperature to form an adhesive layer. In this way, the heat exchanger 1 can be manufactured by bonding the first surface sheet 10, the intermediate sheet 12, and the second surface sheet 14. The heat exchanger 1 is bonded using the solid bonding agent 28, and compared with the conventional case of bonding the cross paths by diffusion bonding, the man-hours can be reduced, and thus the productivity can be further improved.

[0065] The heat exchanger 1 also has a surface sheet 3 and a flow path forming sheet 4 continuously joined at the ends in the X direction and the ends in the Y direction. In the case of this embodiment, the heat exchanger 1 has a welding portion 38 ( Figure 1). In the case of this embodiment, the welding portion 38 joins the first surface sheet 10 and the middle sheet 12, and the middle sheet 12 and the second surface sheet 14 by welding. The shape of the welding portion 38 as viewed from the Z direction is a rectangular shape along the outer edge of the heat exchanger 1, and is formed continuously. There is no particular limitation on welding, and laser welding, resistance welding, ultrasonic welding, etc. can be applied.

[0066] In the heat exchanger 1, although not shown in the figure, the piping is connected to the inlet 16 and the outlet 18 respectively, and the refrigerant is supplied from the cooling system through the piping connected to the inlet 16. The refrigerant flows into the heat exchanger 1 from the inlet 16, flows along the flow path to the outlet 18, and returns to the cooling system from the outlet 18. The periphery of the heat exchanger 1 is sealed by welding, thereby preventing the refrigerant from flowing out to the outside. The refrigerant contacts the first surface sheet 10 and the second surface sheet 14 in the flow path 20, thereby exchanging heat with the outside through the first surface sheet 10 and the second surface sheet 14. The refrigerant is heated and expanded by the heat received from the outside. When the refrigerant expands, the internal pressure of the heat exchanger 1 rises. Since the heat exchanger 1 is joined along the cross path 26 by the adhesive layer, it is possible to suppress the heat exchanger 1 from deforming in the Z direction. The heat exchanger 1 suppresses deformation in the Z direction, so that the refrigerant flowing inside more reliably contacts the inner surfaces of the first surface sheet 10 and the second surface sheet 14, respectively, and flows toward the outlet 18 while changing direction in a zigzag manner in the Y direction along the flow path 20. Therefore, the heat exchanger 1 can perform heat exchange with the outside in a wider range of the surfaces of the first surface sheet 10 and the second surface sheet 14.

[0067] 〈Variation Example〉

[0068] The present invention is not limited to the above-mentioned embodiment, and can be appropriately modified within the scope of the present invention. Figure 2 and Figure 3 The embodiment shown in the figure only needs to have a plurality of intersections 26 extending in a direction intersecting the direction connecting the inlet corresponding portion 22 and the outlet corresponding portion 24. Figure 2 The same structure is marked with the same mark Figure 4 As shown, the flow path 20A has an inlet-side inclined path 40 that is inclined from the inlet corresponding portion 22 to the outlet corresponding portion 24 and extends to one side in the Y direction. Similarly, the flow path 20A has an outlet-side inclined path 42 that is inclined from the outlet corresponding portion 24 to the inlet corresponding portion 22 and extends to the other side in the Y direction. The inlet-side inclined path 40 and the outlet-side inclined path 42 are connected to each other via a plurality of intersections 26.

[0069] The welded portion 38 is not limited to a rectangular shape along the outer edge of the heat exchanger 1, but may also be Figure 4 As shown, it is formed along the outer edge of the flow path 20A. Figure 4The welded portion 38A shown has an inclined portion 44 formed along the inlet side inclined path 40 and the outlet side inclined path 42, and a longitudinal portion 46 along the X direction. The heat exchanger 1 is formed into a shape along the flow path 20A, so that the pressurized area of ​​the surface sheet 3 to which the pressure of the refrigerant acts can be reduced. Therefore, the heat exchanger 1B can suppress the deformation of the surface sheet 3 and the flow path forming sheet 4 in the Z direction due to the pressure of the refrigerant.

[0070] In the above embodiment, the case where the flow path forming sheet 4 includes the intermediate sheet 12 and the second surface sheet 14 is described, but the present invention is not limited thereto. Figure 2 The same structure is marked with the same mark Figure 5 As shown, the flow path forming sheet 4A can also be a structure in which the middle sheet and the second surface sheet are integrated. That is, the flow path forming sheet 4A is a rectangular plate-like component, and has a flow path 20B on the first surface 30 opposite to the surface sheet 3. The flow path 20B is a groove with a bottom surface 48, having an inlet corresponding portion 22, an outlet corresponding portion 24, and a plurality of crossroads 26 extending in a direction intersecting with the direction connecting the inlet corresponding portion 22 and the outlet corresponding portion 24. The flow path 20B does not penetrate in the Z direction. The surface sheet 3 and the flow path forming sheet 4A are joined by an adhesive layer formed by a solid adhesive 28, and are continuously joined at the end in the X direction and the end in the Y direction, thereby integrating. One side of the flow path 20B in the Z direction is closed by the surface sheet 3, and the other side surface in the Z direction is closed by the bottom surface 48 of the flow path 20B.

[0071] In the above-mentioned embodiment, the first surface sheet 10 has an inlet 16 and an outlet 18, but the present invention is not limited thereto. For example, the first surface sheet may have an inlet and the second surface sheet may have an outlet, or the first surface sheet may have an outlet and the second surface sheet may have an inlet.

[0072] [Method for manufacturing heat exchanger]

[0073] Hereinafter, the method for manufacturing the heat exchanger will be described in more detail.

[0074] A method for manufacturing a heat exchanger in one embodiment includes a pre-joining step and a joining step. In the pre-joining step, a laminated body is prepared in which a first component (surface sheet), a solid adhesive, and a second component (flow path forming sheet) are sequentially arranged, the solid adhesive having at least one amorphous thermoplastic resin selected from thermoplastic epoxy resin and phenoxy resin as a main component, and the second component is to be joined to the first component. In the joining step, the laminated body is heated and pressurized to melt the solid adhesive and join the first component to the second component. In the pre-joining step, the first component and the solid adhesive and the second component and the solid adhesive are not joined, but joined in the next joining step. The solid adhesive may have viscosity, in which case the solid adhesive is temporarily fixed to the substrate in the pre-joining step.

[0075] 〈Pre-joining process〉

[0076] In the pre-bonding step, a laminated body is formed in which a first component, a solid adhesive, and a second component are sequentially arranged, wherein the solid adhesive mainly comprises at least one amorphous thermoplastic resin selected from thermoplastic epoxy resins and phenoxy resins. In the laminated body, the first component and the solid adhesive, and the solid adhesive and the second component are not bonded to each other, and are in a state where independent components overlap.

[0077] The solid adhesive is solid at room temperature, that is, has no fluidity at 23° C. without pressure. The solid adhesive preferably has the property of maintaining its shape without deformation for more than 30 days at 23° C. without pressure and does not deteriorate.

[0078] The above-mentioned "main component" refers to the component with the highest content in the resin component in the solid adhesive, and is a component whose content in the resin component in the solid adhesive is 50% by mass or more. The solid adhesive preferably contains 50% by mass or more of the resin component, more preferably 70% by mass or more, further preferably 80% by mass or more, and particularly preferably 90% by mass or more.

[0079] (Solid adhesive)

[0080] The solid bonding agent is mainly composed of at least one amorphous thermoplastic resin selected from thermoplastic epoxy resins and phenoxy resins, the epoxy equivalent of the amorphous thermoplastic resin is 1,600 or more, or the amorphous thermoplastic resin does not contain epoxy groups, and the heat of fusion of the amorphous thermoplastic resin is 15 J / g or less. In the previous bonding using liquid adhesives, bubbles may be mixed into the bonding part, or if there are unevenness on the surface of the metal parts, the bonded metal parts may be grounded. The mixing of bubbles into the bonding part or the grounding between the metal parts may cause galvanic corrosion between different types of metal parts. In the present disclosure, by using a solid bonding agent mainly composed of at least one amorphous thermoplastic resin selected from thermoplastic epoxy resins and phenoxy resins, the mixing of bubbles can be prevented, the unevenness on the surface of the metal parts can be absorbed by the thickness of the solid bonding agent, and the metal parts can be bonded to each other. Therefore, according to the present disclosure, contact between metal parts can be prevented, and galvanic corrosion that may occur between different types of metal parts can be suppressed.

[0081] The amorphous resin in the present disclosure is a resin that has a melting point (Tm) but does not have a clear endothermic peak associated with melting or the endothermic peak is very small in the measurement using a differential scanning calorimeter (DSC). The heat of fusion is calculated from the area of ​​the endothermic peak of DSC and the mass of the thermoplastic resin component. In the case where the solid adhesive contains an inorganic filler, etc., the heat of fusion is calculated from the mass of the resin component excluding the inorganic filler.

[0082] Specifically, the amorphous thermoplastic resin in the present disclosure refers to a resin having the properties measured by the following steps. 2 to 10 mg of a sample is weighed and placed in an aluminum pan, and the temperature is raised from 23°C to 200°C or higher at 10°C / min using a DSC (DSC8231 manufactured by Rigaku Corporation) to obtain a DSC curve. Next, when the heat of fusion is calculated based on the area of ​​the endothermic peak at the time of melting obtained from the DSC curve and the above-mentioned weighed value, a resin with a heat of fusion of 15 J / g or less is considered to be an amorphous thermoplastic resin.

[0083] From the viewpoint of sufficiently imparting the properties of the amorphous thermoplastic resin to the solid adhesive, the content of the amorphous thermoplastic resin in the resin component in the solid adhesive is preferably 60 mass % or more, more preferably 70 mass % or more, further preferably 80 mass % or more, and most preferably 90 mass % or more.

[0084] The heat of fusion is 15 J / g or less, preferably 11 J / g or less, more preferably 7 J / g or less, further preferably 4 J / g or less, and most preferably the endothermic peak during melting is below the detection limit.

[0085] The epoxy equivalent is 1,600 or more, preferably 2,000 or more, more preferably 5,000 or more, further preferably 9,000 or more, and most preferably it is more than the detection limit and epoxy groups are not substantially detected.

[0086] By using the above-mentioned solid adhesive, when heated, the viscosity does not drop sharply as seen in conventional hot melt adhesives, and even in a high temperature range exceeding 200°C, the viscosity does not become low (0.001 to 100 Pa·s). Therefore, the solid adhesive does not flow out of the laminate even in a molten state, and the thickness of the adhesive layer can be stably ensured, and a high adhesive force can be stably obtained. As a result, contact between metal parts can be more reliably prevented to prevent electrical corrosion, and a high adhesive force can be stably obtained.

[0087] The epoxy equivalent in the present disclosure (the mass of the above-mentioned resin containing 1 mol of epoxy groups) is the value of the epoxy equivalent of the thermoplastic epoxy resin or phenoxy resin component contained in the solid adhesive before bonding, and is a value measured by the method specified in JIS K 7236:2001 (the unit is "g / eq."). Specifically, the epoxy equivalent of the resin is measured using a potentiometric titration apparatus, cyclohexanone as a solvent, a tetraethylammonium bromide acetic acid solution is added to the resin, and a 0.1 mol / L perchloric acid-acetic acid solution is used. For solvent-diluted products (resin varnishes), the value is calculated based on the non-volatile component as a solid content conversion value. The epoxy equivalent of a mixture of two or more resins can also be calculated from the content of each resin and the epoxy equivalent.

[0088] The melting point of the amorphous thermoplastic resin as the main component of the solid adhesive is preferably 50°C to 400°C, more preferably 60°C to 350°C, and even more preferably 70°C to 300°C. When the melting point is within the range of 50°C to 400°C, the solid adhesive is efficiently deformed and melted by heating, and effectively wets and spreads on the bonding surface, so that a high adhesive force can be obtained. In the present disclosure, the melting point of the amorphous thermoplastic resin refers to the temperature at which it softens from a substantially solid state and becomes thermoplastic, and can be melted and bonded.

[0089] In a joint body containing a conventional thermosetting adhesive, it is difficult to disassemble the joint body and to recycle the different materials constituting the joint body separately (i.e., poor recyclability). In addition, when a thermosetting adhesive is used, when there is an offset of the joint portion during the manufacturing process of the joint body, or when there is a defect on the adherend and it needs to be replaced, it is difficult to re-paste (i.e., poor repairability), which lacks convenience. On the other hand, the above-mentioned solid adhesive can be softened and melted by heat, and two adherends can be easily separated, so it has excellent recyclability. In addition, since the above-mentioned solid adhesive is thermoplastic, it can be reversibly softened, melted and hardened (cured) repeatedly, and it also has excellent repairability.

[0090] 《Thermoplastic Epoxy Resin》

[0091] The thermoplastic epoxy resin is preferably a polymer of the following (a) and (b), wherein (a) is a bifunctional epoxy resin monomer or oligomer, and (b) is a bifunctional compound having two identical or different functional groups selected from phenolic hydroxyl, carboxyl, mercapto, isocyanate and cyanate groups. By using this compound, a polymerization reaction to form a linear polymer can be preferentially performed to form a thermoplastic epoxy resin having desired properties.

[0092] The above-mentioned (a) bifunctional epoxy resin monomer or oligomer refers to an epoxy resin monomer or oligomer having two epoxy groups in the molecule. Examples of the above-mentioned (a) bifunctional epoxy resin monomer or oligomer include bisphenol A type epoxy resin, bisphenol F type epoxy resin, bifunctional phenol novolac type epoxy resin, bisphenol AD ​​type epoxy resin, biphenyl type epoxy resin, bifunctional naphthalene type epoxy resin, bifunctional alicyclic epoxy resin, bifunctional glycidyl ester type epoxy resin (e.g. diglycidyl phthalate, diglycidyl tetrahydrophthalate, diglycidyl dimer acid diglycidyl ester, etc.), difunctional glycidyl amine type epoxy resin (e.g. diglycidyl aniline, diglycidyl toluidine, etc.), bifunctional heterocyclic epoxy resin, bifunctional diaryl sulfone type epoxy resin, hydroquinone type epoxy resin (e.g. hydroquinone diglycidyl ether, 2,5-dihydroquinone diglycidyl ether, etc.), and difunctional diphenyl ether type epoxy resin. tert-butylhydroquinone diglycidyl ether, resorcinol diglycidyl ether, etc.), difunctional alkylene glycidyl ether compounds (for example, butanediol diglycidyl ether, butenediol diglycidyl ether, butynediol diglycidyl ether, etc.), difunctional glycidyl group-containing hydantoin compounds (for example, 1,3-diglycidyl-5,5-dialkylhydantoin, 1-glycidyl-3-(glycidyloxyalkyl)-5,5-dialkylhydantoin, etc.), difunctional glycidyl group-containing siloxanes (for example, 1,3-bis(3-glycidyloxypropyl)-1,1,3,3-tetramethyldisiloxane, α,β-bis(3-glycidyloxypropyl)polydimethylsiloxane, etc.), and modified products thereof. Among them, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin and biphenyl type epoxy resin are preferred from the viewpoint of reactivity and handleability.

[0093] Examples of the bifunctional compound having a phenolic hydroxyl group of (b) include mononuclear aromatic dihydroxy compounds having one benzene ring such as catechol, resorcinol, and hydroquinone, bisphenol compounds such as bis(4-hydroxyphenyl)propane (bisphenol A), bis(4-hydroxyphenyl)methane (bisphenol F), and bis(4-hydroxyphenyl)ethane (bisphenol AD), compounds having a condensed ring such as dihydroxynaphthalene, bifunctional phenol compounds into which an allyl group is introduced such as diallylresorcinol, diallylbisphenol A, and triallyldihydroxybiphenyl, and dibutylbisphenol A.

[0094] Examples of the bifunctional compound having a carboxyl group (b) include adipic acid, succinic acid, malonic acid, cyclohexanedicarboxylic acid, phthalic acid, isophthalic acid, and terephthalic acid.

[0095] Examples of the bifunctional compound having a mercapto group (b) include ethylene glycol dithioacetate and ethylene glycol dithiopropionate.

[0096] Examples of the bifunctional compound having an isocyanate group (b) include diphenylmethane diisocyanate (MDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HMDI) and toluene diisocyanate (TDI).

[0097] Examples of the bifunctional compound having a cyanate group (b) include 2,2-bis(4-cyanophenyl)propane, 1,1-bis(4-cyanophenyl)ethane, and bis(4-cyanophenyl)methane.

[0098] In the above (b), the bifunctional compound having a phenolic hydroxyl group can form a thermoplastic polymer having appropriate properties. Therefore, from the viewpoint of heat resistance and adhesion, a bifunctional compound having two phenolic hydroxyl groups and a bisphenol structure or a biphenyl structure is preferred. From the viewpoint of heat resistance and cost, bisphenol A, bisphenol F and bisphenol S are preferred.

[0099] When (a) is bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin or biphenyl epoxy resin, and (b) is bisphenol A, bisphenol F or bisphenol S, the polymer obtained by polymerization of (a) and (b) has a p-phenylene structure and an ether bond as the main skeleton, a main chain formed by these alkylene groups, and a structure in which a hydroxyl group generated by addition polymerization is arranged on the side chain. The mechanical strength of the polymer after polymerization can be improved by the straight-chain structure produced by the main skeleton having the phenylene structure and the ether bond, and the adhesion to the substrate can be improved by the hydroxyl group arranged on the side chain. As a result, it is possible to achieve a high bonding strength at the same level as a thermosetting resin while maintaining operability. In addition, by utilizing heat to soften and melt it, recycling and repair can be achieved, and the recyclability and repairability that are problems in thermosetting resins can be improved.

[0100] 《Phenoxy resin》

[0101] Phenoxy resin is a polyhydroxy polyether synthesized from bisphenol compounds and epichlorohydrin, and has thermoplasticity. As a method for manufacturing phenoxy resin, there are known methods for direct reaction of dihydric phenol compounds with epichlorohydrin and methods for addition polymerization of diglycidyl ether of dihydric phenol compounds with dihydric phenol compounds, and phenoxy resin can be obtained by any method. In the case of direct reaction of dihydric phenol compounds with epichlorohydrin, as dihydric phenol compounds, for example, phenol compounds such as bisphenol A, bisphenol F, bisphenol S, biphenol, biphenol, and fluorene diphenyl can be cited. Among them, from the viewpoint of cost, adhesion, viscosity and heat resistance, bisphenol A, bisphenol F and bisphenol S are preferred. In addition to dihydric phenol compounds, aliphatic diols such as ethylene glycol, propylene glycol, and diethylene glycol can also be contained in the above-mentioned direct reaction. These can be used alone or in combination of two or more. Phenoxy resin has a chemical structure similar to that of epoxy resin, and has a main skeleton composed of a p-phenylene structure and an ether bond, and has a main chain formed by connecting these and a structure in which hydroxyl groups are arranged on side chains.

[0102] 《Thermoplastic epoxy resins and phenoxy resins》

[0103] The weight average molecular weight of the thermoplastic epoxy resin and the phenoxy resin is preferably 10,000 to 500,000, more preferably 18,000 to 300,000, and further preferably 20,000 to 200,000, based on the polystyrene conversion value measured by GPC (gel permeation chromatography). The weight average molecular weight is a standard polystyrene conversion value calculated based on the dissolution peak position detected by GPC. If the weight average molecular weight is within the above range, the balance between thermoplasticity and heat resistance is good, so it is possible to form a joint body by melting efficiently, and the heat resistance of the joint body can also be improved. If the weight average molecular weight is 10,000 or more, the heat resistance is excellent, and if it is 500,000 or less, the viscosity during melting is low, and the adhesion becomes high.

[0104] 《Method for producing solid adhesive》

[0105] There is no particular limitation on the method for producing the solid adhesive, and the solid adhesive can be obtained, for example, by heating a monomer or oligomer of a bifunctional epoxy compound to polymerize it. A solvent may also be added to reduce the viscosity during polymerization to facilitate stirring. When a solvent is added, it needs to be removed, and the solid adhesive can be obtained by drying or polymerizing or both on a release film or the like.

[0106] As required, other additives may be added to the solid adhesive within a range that does not hinder the effect of the present invention. The amount of the additive is preferably 50% by volume or less, more preferably 30% by volume or less, further preferably 20% by volume or less, and most preferably 10% by volume or less relative to the total amount of the amorphous thermoplastic resin. In the present disclosure, the volume % of the additive represents the volume ratio of the additive contained before the polymerization of the monomer or oligomer of the bifunctional epoxy compound based on the total volume of the amorphous thermoplastic resin, and the volume of the additive can be obtained by dividing the mass of the additive contained by the true specific gravity of the additive.

[0107] As the above-mentioned additives, for example, viscosity modifiers, inorganic fillers, organic fillers (resin powders), defoamers, coupling agents such as silane coupling agents, and pigments can be cited. These additives can be used alone or in combination of two or more. As a viscosity modifier, for example, a reactive diluent can be cited. As an inorganic filler, for example, spherical fused silica, metal powders of metals such as iron, silica sand, talc, calcium carbonate, mica, acid clay, diatomaceous earth, kaolin, quartz, titanium oxide, silicon dioxide, phenolic resin microspheres, and glass balls can be cited.

[0108] The solid adhesive thus obtained has a low content of unreacted monomers or terminal epoxy groups, or contains substantially no unreacted monomers or terminal epoxy groups, and therefore has excellent storage stability and can be stored for a long period of time at room temperature.

[0109] The form of the solid adhesive before melting is not particularly limited, but preferably has any shape selected from a film, a rod, a granule, and a powder. At least one side of the outer shape of the solid adhesive is preferably 5 mm or less, more preferably 3 mm or less, further preferably 1 mm or less, particularly preferably 0.5 mm or less, and most preferably 0.3 mm or less. By clamping the solid adhesive having at least one side of the outer shape of 5 mm or less between the first component and the second component and heating and pressurizing, the solid adhesive is effectively spread on the bonding surface, so that a high bonding force can be obtained.

[0110] The solid adhesive before melting preferably has a film shape. The solid adhesive in a film shape can join the metal parts to be joined while firmly holding the metal parts to be joined at a predetermined interval on the entire joining surface. Therefore, the solid adhesive in a film shape is particularly advantageous for preventing electrical corrosion. The thickness of the solid adhesive in a film shape is preferably 10μm to 5mm, more preferably 20μm to 3mm, and further preferably 30μm to 0.5mm. By making the thickness of the solid adhesive in a film shape greater than 10μm, electrical corrosion between the first component and the second component can be more effectively prevented, and the bonding strength can be ensured. By making the thickness of the solid adhesive in a film shape less than 5mm, the bonding strength in the shear direction of the joining surface can be increased.

[0111] The solid adhesive may have viscosity within a range that does not impair the adhesive force and heat resistance. In this case, the solid adhesive may be temporarily fixed to the base material in the laminate preparation step.

[0112] 〈Joining process〉

[0113] In the bonding step, the stacked body is heated and pressurized to melt the solid bonding agent, and then the temperature is lowered to solidify the solid bonding agent, thereby bonding the first member and the second member.

[0114] The temperature of the heating and pressurizing is preferably 100° C. to 400° C., more preferably 120° C. to 350° C., and even more preferably 150° C. to 300° C. By heating at 100° C. to 400° C., the solid adhesive is efficiently deformed and melted, and effectively wets and diffuses on the bonding surface, thereby obtaining high bonding strength.

[0115] The pressure of the heating and pressurizing is preferably 0.01MPa to 20MPa, more preferably 0.1MPa to 10MPa, and further preferably 0.2MPa to 5MPa. The pressure here refers to the average pressure of the bonding surface of the first component and the second component. By applying pressure at 0.01MPa to 20MPa, the solid adhesive is effectively deformed and effectively infiltrates and diffuses on the bonding surface, so that a high bonding force can be obtained. In the case where at least one of the first component or the second component contains a thermoplastic resin on the bonding surface, by applying pressure at 0.01MPa to 20MPa, the solid adhesive is dissolved with the thermoplastic resin of the component, and a high bonding force can be obtained.

[0116] Thermoplastic epoxy resins and phenoxy resins, which are main components of solid adhesives, have low cohesive force within the resin and have hydroxyl groups, so they interact strongly with the substrate and can bond dissimilar materials with higher adhesive strength than conventional crystalline hot melt adhesives.

[0117] The bonding of the first member and the second member utilizes the phase change (solid-liquid-solid) of the solid bonding agent, and since it is not accompanied by a chemical reaction, the bonding can be completed in a shorter time compared to conventional thermosetting epoxy resins.

[0118] The thickness of the solid adhesive after bonding is preferably 10 μm to 5 mm, more preferably 20 μm to 3 mm, and further preferably 30 μm to 0.5 mm. By setting the thickness of the solid adhesive after bonding to 10 μm or more, it is possible to more reliably prevent electrical corrosion between the first component and the second component, and to ensure bonding strength. By setting the thickness of the solid adhesive after bonding to 5 mm or less, it is possible to increase the bonding strength in the shear direction of the bonding surface, and to more reliably maintain the flow path of the heat exchanger.

[0119] [Heat exchanger (joined body 1)]

[0120] Figure 6 is a schematic cross-sectional view showing a state where the first component 3 and the second component 4 are bonded via the solid bonding agent, and is a view showing, for example, Figure 1 FIG. 1 is a diagram showing the joint between the surface sheet and the flow path forming sheet. Figure 6 In the joint body 1 shown, the first part 3 and the second part 4 are joined and integrated via the adhesive layer 2 formed by the solid adhesive being melted and solidified, and the joint body 1 of the first part 3 and the second part 4 shows excellent joint strength. In addition to being affected by the strength of the interface interaction between the adhesive layer and the substrate, the joint strength is also affected by various factors such as the thickness of the adhesive layer, the molecular weight and chemical structure of the polymer constituting the adhesive, mechanical properties, and viscoelastic properties. Therefore, the detailed mechanism of the joint body 1 disclosed in the present invention showing excellent joint strength is still unclear, and it is speculated that the main reason is that the amorphous thermoplastic resin constituting the adhesive layer has low cohesive force, and there are hydroxyl groups in the resin, forming chemical bonds or intermolecular forces such as hydrogen bonds and van der Waals forces at the interface between the adhesive layer and the first part and the interface between the adhesive layer and the second part. However, in the joint body 1, the state or characteristics of the interface of the joint body 1 are caused by the extremely thin chemical structure with a thickness of less than nanometer level, and therefore are difficult to analyze. Under the current technology, it is impossible or impractical to determine the state or characteristics of the interface of the joint body 1 disclosed herein and to distinguish it from the joint body 1 that does not contain the solid bonding agent disclosed herein.

[0121] The heat exchanger of the present disclosure whose adhesive layer includes an amorphous thermoplastic resin has excellent recyclability and repairability, and can be easily decomposed into the first member and the second member, that is, the surface sheet and the flow path forming sheet, by heating the bonded body 1 .

[0122] Example

[0123] The following are test examples and comparative test examples related to the present invention, but the present invention is not limited thereto. In the following examples, the first member and the second member are collectively referred to as a bonding substrate.

[0124] 〈Bonding base material〉

[0125] The following bonding substrates were used.

[0126] (1) Part 1

[0127] "aluminum"

[0128] The surface of aluminum alloy A6061-T6 (Young's modulus: 68.3 GPa) was subjected to sandblasting to obtain a test piece having a width of 18 mm, a length of 45 mm, and a thickness of 1.5 mm.

[0129] (2) Part 2

[0130] 《PC (Polycarbonate)》

[0131] SABIC 121R was injection molded to obtain a test piece having a width of 10 mm, a length of 45 mm, and a thickness of 3 mm, and was used without performing surface treatment.

[0132] "aluminum"

[0133] The surface of aluminum alloy A6061-T6 (Young's modulus: 68.3 GPa) was subjected to sandblasting to obtain a test piece having a width of 10 mm, a length of 45 mm, and a thickness of 3 mm.

[0134] 〈Weight average molecular weight, heat of fusion and epoxy equivalent of thermoplastic epoxy resin and phenoxy resin〉

[0135] The weight average molecular weight, heat of fusion and epoxy equivalent of the thermoplastic epoxy resin and phenoxy resin were determined by the following procedures, respectively.

[0136] (Weight average molecular weight)

[0137] The thermoplastic epoxy resin and the phenoxy resin were dissolved in tetrahydrofuran, and the results were measured under the following conditions using Prominence 501 (manufactured by Showa Kagaku K.K., Detector: Shodex (registered trademark) RI-501 (manufactured by Showa Denko K.K.)).

[0138] Column: LF-804 manufactured by Showa Denko K.K. × 2

[0139] Column temperature: 40°C

[0140] Sample: 0.4 mass% tetrahydrofuran solution of resin

[0141] Flow rate: 1mL / min

[0142] Eluent: Tetrahydrofuran

[0143] Calibration method: Convert with standard polyethylene

[0144] (Heat of Fusion)

[0145] 2 to 10 mg of a thermoplastic epoxy resin and a phenoxy resin were weighed and placed in an aluminum pan, and the temperature was raised from 23°C to 200°C at a rate of 10°C / min using a DSC (DSC8231 manufactured by Rigaku Corporation) to obtain a DSC curve. The heat of fusion was calculated from the area of ​​the endothermic peak during melting of the obtained DSC curve and the weighed value.

[0146] (Epoxy Equivalent Weight)

[0147] The measured value obtained in accordance with JIS K 7236: 2001 was converted into a value of resin solid content. In the case of a simple mixture without reaction, it was calculated from the respective epoxy equivalents and contents.

[0148] <Implementation Test Example 1>

[0149] (Solid adhesive P-1)

[0150] 203 g (1.0 equivalent) of jER (registered trademark) 1007 (Mitsubishi Chemical Corporation, bisphenol A type epoxy resin, weight average molecular weight of about 10,000), 12.5 g (1.0 equivalent) of bisphenol S, 2.4 g of triphenylphosphine and 1,000 g of methyl ethyl ketone were added to a reaction apparatus equipped with a stirrer, a reflux cooler, a gas inlet pipe and a thermometer, and the mixture was heated to 100°C while stirring in a nitrogen atmosphere. Dissolution was visually confirmed, and the mixture was cooled to 40°C to obtain a resin composition having a solid content of about 20% by mass. The solvent was removed from the resin composition, and the mixture was heated at 160°C for 2 hours to obtain a film-like solid adhesive (P-1) having a solid content of 100% by mass and a thickness of 100 μm. The weight average molecular weight was about 37,000. The epoxy equivalent was above the detection limit. No melting heat peak was detected in DSC.

[0151] (Joint body)

[0152] The following two types of joints were produced. For the evaluation of the open time, a solid bonding agent was placed on the above-mentioned aluminum substrate (first component) and then left to stand for 3 days, and then the above-mentioned aluminum substrate (second component) was placed. In addition, the same steps as the following "metal / metal" were followed to produce a joint for open time evaluation.

[0153] Metal / Metal

[0154] The solid adhesive P-1 cut into a size of 10×15 mm was placed on the aluminum substrate (first component), and then the aluminum substrate (second component) was quickly placed thereon. The overlap between these substrates was 10 mm in width and 5 mm in depth. The solid adhesive P-1 was placed so as to cover all overlapping areas between the substrates. That is, the first component and the second component were not in direct contact with each other, and an unbonded laminate was prepared with the solid adhesive sandwiched therebetween.

[0155] A high-frequency induction welding machine (manufactured by Seidensha Electronics Co., Ltd., oscillator UH-2.5K, punch press JIIP30S) was used to heat the metal by high-frequency induction, and the test pieces were joined together by heating and pressurizing. The pressure was 110N (pressure 2.2MPa), the oscillation frequency was 900kHz, and the oscillation time was 5 seconds.

[0156] 《Metal / Resin》

[0157] A bonded body was obtained in the same manner as the above-mentioned <metal / metal> bonded body except that the above-mentioned aluminum substrate was used as the first component and the above-mentioned PC substrate was used as the second component.

[0158] <Implementation Test Example 2>

[0159] (Solid adhesive P-2)

[0160] In a reaction apparatus equipped with a stirrer, a reflux cooler, a gas inlet pipe and a thermometer, 20 g of フェノトート (registered trademark) YP-50S (manufactured by Nippon Steel Chemical & Materials Co., Ltd., a phenoxy resin with a weight average molecular weight of about 50,000) and 80 g of cyclohexanone were added, and the temperature was raised to 60°C while stirring, and the dissolution was visually confirmed, and the mixture was cooled to 40°C to obtain a resin composition with a solid content of 20% by mass. The solvent was removed from the resin composition to obtain a film-like solid adhesive (P-2) with a solid content of 100% by mass and a thickness of 100 μm. The weight average molecular weight was 50,000, and the epoxy equivalent was above the detection limit. No melting heat peak was detected in DSC.

[0161] (Joint body)

[0162] Joined bodies and joined bodies for open time evaluation shown in Table 1 were prepared in the same manner as in Test Example 1 except that P-2 was used as the solid bonding agent.

[0163] <Implementation Test Example 3>

[0164] (Solid adhesive P-3)

[0165] The resin composition P-2 and crystalline epoxy resin YSLV-80XY (manufactured by Nippon Steel Chemical & Materials Co., Ltd.) were mixed at a mass ratio of 98:2 to obtain a solid adhesive (P-3) having a weight average molecular weight of 36,000, an epoxy equivalent of 9600 g / eq, and a heat of fusion of 2 J / g.

[0166] (Joint body)

[0167] Joined bodies and joined bodies for open time evaluation shown in Table 1 were prepared in the same manner as in Test Example 1 except that P-3 was used as the solid bonding agent.

[0168] <Implementation Test Example 4>

[0169] (Solid adhesive P-4)

[0170] The resin composition P-2 and crystalline epoxy resin YSLV-80XY (manufactured by Nippon Steel Chemical & Materials Co., Ltd.) were mixed at a mass ratio of 94:6 to obtain a solid adhesive (P-4) having a weight average molecular weight of 35,000, an epoxy equivalent of 2100 g / eq, and a heat of fusion of 4 J / g.

[0171] (Joint body)

[0172] Joined bodies and joined bodies for open time evaluation shown in Table 1 were prepared in the same manner as in Test Example 1 except that P-4 was used as the solid bonding agent.

[0173] <Implementation Test Example 5>

[0174] (Solid adhesive P-5)

[0175] The resin composition P-2 and crystalline epoxy resin YSLV-80XY (manufactured by Nippon Steel Chemical & Materials Co., Ltd.) were mixed at a mass ratio of 89:11 to obtain a solid adhesive (P-5) having a weight average molecular weight of 33,000, an epoxy equivalent of 1745 g / eq, and a heat of fusion of 11 J / g.

[0176] (Joint body)

[0177] Joined bodies and joined bodies for open time evaluation shown in Table 1 were prepared in the same manner as in Test Example 1 except that P-5 was used as the solid bonding agent.

[0178] <Implementation Test Example 6>

[0179] (Solid adhesive P-6)

[0180] 203 g (1.0 equivalent) of jER (registered trademark) 1007 (Mitsubishi Chemical Corporation, bisphenol A type epoxy resin, molecular weight of about 4060), 12.5 g (0.6 equivalent) of bisphenol S (molecular weight 250), 2.4 g of triphenylphosphine and 1,000 g of methyl ethyl ketone were added to a reaction apparatus equipped with a stirrer, a reflux cooler, a gas introduction tube and a thermometer, and the mixture was heated to 100°C while stirring in a nitrogen atmosphere. Dissolution was visually confirmed, and the mixture was cooled to 40°C to obtain a resin composition having a solid content of about 20% by mass. The solvent was removed from the resin composition, and the mixture was heated at 160°C for 2 hours to obtain a film-like solid adhesive (P-6) having a solid content of 100% by mass and a thickness of 100 μm. The weight average molecular weight was about 30,000, and the epoxy equivalent was above the detection limit. No melting heat peak was detected in DSC.

[0181] (Joint body)

[0182] Joined bodies and joined bodies for open time evaluation shown in Table 1 were prepared in the same manner as in Test Example 1 except that P-6 was used as the solid bonding agent.

[0183] <Comparative Test Example 1>

[0184] (Solid Adhesive Q-1)

[0185] Two liquids of thermosetting liquid epoxy adhesive E-250 (manufactured by Konishi Co., Ltd., a two-liquid type of bisphenol epoxy resin and amine curing agent) were mixed, applied to a release film, cured at 100°C for 1 hour, cooled, and peeled off from the release film to obtain a thin film-like solid adhesive (Q-1) with a thickness of 100 μm. No melting heat peak was detected in DSC. The epoxy equivalent and weight average molecular weight could not be measured because it was insoluble in the solvent.

[0186] (Joint body)

[0187] Joined bodies and joined bodies for open time evaluation shown in Table 1 were prepared in the same manner as in Test Example 1 except that Q-1 was used as the solid bonding agent.

[0188] <Comparative Test Example 2>

[0189] (Solid Adhesive Q-2)

[0190] An amorphous polycarbonate film (Iupilon (registered trademark) FE2000, manufactured by Mitsubishi Engineering-Plastics Corporation, thickness 100 μm) was used as the solid adhesive Q-2. No melting heat peak was detected in DSC.

[0191] (Joint body)

[0192] Joined bodies and joined bodies for open time evaluation shown in Table 1 were prepared in the same manner as in Test Example 1 except that Q-2 was used as the solid bonding agent.

[0193] <Comparative Test Example 3>

[0194] (Solid Adhesive Q-3)

[0195] Crystalline epoxy resin YSLV-80XY (manufactured by Nippon Steel Chemical & Materials Co., Ltd.) was used as the solid adhesive (Q-3). The epoxy equivalent was 192 g / eq. The weight average molecular weight was 340. The heat of fusion was 70 J / g.

[0196] (Joint body)

[0197] Joined bodies and joined bodies for open time evaluation shown in Table 1 were prepared in the same manner as in Test Example 1 except that Q-3 was used as the solid bonding agent.

[0198] <Comparative Test Example 4>

[0199] (Joint body)

[0200] Two liquids of thermosetting liquid epoxy adhesive E-250 (manufactured by Konishi Co., Ltd., a two-liquid type of bisphenol epoxy resin and amine curing agent) were mixed and applied to the first component and the second component similar to the above-mentioned Implementation Test Example 1, respectively, and then bonded within 1 minute, and then allowed to stand in an oven at 100°C for 1 hour while being fixed with a clamp to cure the adhesive component, and then cooled to room temperature to prepare the bonded bodies shown in Table 1. Bonded bodies for open time evaluation were prepared in the same manner as above, except that the thermosetting liquid epoxy adhesive E-250 was applied to the first component and the second component, respectively, and then allowed to stand for 3 days before bonding.

[0201] <Comparative Test Example 5>

[0202] 203 g (1.0 equivalent) of jER (registered trademark) 1007 (manufactured by Mitsubishi Chemical Corporation, bisphenol A type epoxy resin, weight average molecular weight of about 10,000), 12.5 g (1.0 equivalent) of bisphenol S, 2.4 g of triphenylphosphine and 1,000 g of methyl ethyl ketone were added to a flask and stirred at room temperature to obtain a liquid resin composition having a solid content of about 20% by mass. The liquid resin composition was applied to the second component similar to the above-mentioned test example 1, dried at room temperature for 30 minutes, and then allowed to stand in an oven at 160°C for 2 hours, thereby forming a solid thermoplastic epoxy resin polymer coating with a thickness of 100 μm on the surface of the second component. The weight average molecular weight of the coating is about 40,000. The epoxy equivalent is above the detection limit. No melting heat peak was detected in the DSC.

[0203] (Joint body)

[0204] The bonded bodies shown in Table 1 were prepared in the same manner as in Test Example 1, except that the first component was directly arranged on the second component having the above coating. In order to evaluate the open time, a bonded body for open time evaluation was prepared in the same manner as above, except that the thermoplastic epoxy resin polymer coating was formed on the surface of the second component, left to stand for 3 days, and then laminated with the first component.

[0205] <Comparative Test Example 6>

[0206] In a reaction apparatus equipped with a stirrer, a reflux cooler, a gas inlet pipe and a thermometer, 20 g of フェノトート (registered trademark) YP-50S (manufactured by Nippon Steel Chemical & Materials Co., Ltd., a phenoxy resin with a weight average molecular weight of about 50,000) and 80 g of cyclohexanone were added, and the temperature was raised to 60°C while stirring, and the dissolution was visually confirmed, and the mixture was cooled to 40°C to obtain a liquid resin composition with a solid content of 20% by mass. On the second component similar to the above-mentioned implementation example 1, the above-mentioned liquid resin composition was scraped and allowed to stand in an oven at 70°C for 30 minutes, thereby forming a phenoxy resin coating with a thickness of 100 μm on the surface of the second component. The weight average molecular weight of the coating is about 50,000. The epoxy equivalent is above the detection limit. No melting heat peak was detected in DSC.

[0207] (Joint body)

[0208] The joined bodies shown in Table 1 were prepared in the same manner as in Test Example 1, except that the first member was directly disposed on the second member having the phenoxy resin coating. In order to evaluate the open time, a joined body for open time evaluation was prepared in the same manner as above, except that the phenoxy resin coating was formed on the surface of the second member, left to stand for 3 days, and then laminated with the first member.

[0209] <Comparative Test Example 7>

[0210] (Joint body)

[0211] The bonded bodies and bonded bodies for open time evaluation shown in Table 1 were prepared in the same manner as in Test Example 1 except that crystalline polyamide hot melt adhesive film NT-120 (manufactured by Japan Matai Co., Ltd., thickness 100 μm) was used as the solid bonding agent. The heat of fusion was 60 J / g.

[0212] [Shear Adhesion]

[0213] After the bonded bodies obtained in Test Examples 1 to 6 and Comparative Test Examples 1 to 7 were left to stand at a measurement temperature (23°C) for more than 30 minutes, a tensile shear bond strength test was performed in an atmosphere of 23°C using a tensile testing machine (universal testing machine Autograph "AG-Xplus" (manufactured by Shimadzu Corporation); load cell 10 kN, tensile speed 10 mm / min) in accordance with ISO19095 to measure the bond strength. The measurement results are shown in Table 1.

[0214] [Joining process time]

[0215] The bonding process time is measured as follows. The time from the start point to the end point is measured, with the time when the bonding agent first contacts one or both substrates constituting the bonded body as the starting point and the time when the bonded body is completed as the end point. With respect to the heating and pressing time, the values ​​of the bonded bodies shown in Table 1 are averaged.

[0216] [Recyclability]

[0217] After the bonded bodies shown in Table 1 were placed on a hot plate at 200° C. and heated for 1 minute, it was determined whether they could be easily peeled off with a force of 1 N or less. If peeling was possible, it was good (OK), and if not peeling was not good (NG).

[0218] [Restorability]

[0219] In each aluminum test piece (a layer of bonding solid remains on the surface of the first component or the second component or both) whose bonding surface is broken after the test at 23°C in the above-mentioned tensile shear strength test, the first component is arranged on the second component, and a bonded body is prepared in the same manner as in the above-mentioned Implementation Test Example 1 to obtain a repaired bonded body. The shear adhesion at 23°C of the above-mentioned repaired bonded body is measured in the same manner as in the above-mentioned test method, and if it is 80% or more of the first shear adhesion, it is good (OK), and if it is less than 80%, it is not good (NG).

[0220] [Opening hours evaluation]

[0221] The above tensile shear bonding strength test was performed at 23°C using the joint body for open time evaluation. Compared with the test pieces prepared by the methods of the above implementation test examples and comparative test examples, if the shear bonding strength is 80% or more, it is good (OK), and if it is less than 80%, it is not good (NG). The open time evaluation of good (OK) means that the open time is long and the convenience is excellent.

[0222]

[0223]

[0224] According to the present invention, a heat exchanger in which a surface sheet (first member) and a flow path forming sheet (second member) are firmly bonded can be manufactured with a short bonding process time and a long open time.

[0225] Industrial Availability

[0226] The present invention can be utilized in a method for manufacturing a heat exchanger.

[0227] Description of Reference Numerals

[0228] 1Joint body (heat exchanger)

[0229] 1A Heat Exchanger

[0230] 2 Adhesive layer

[0231] 3Part 1 (surface sheet)

[0232] 4. The second component (flow path forming sheet)

[0233] 4A flow path forming sheet

[0234] 101st surface sheet

[0235] 12 Middle sheet

[0236] 14 2nd surface sheet

[0237] 16 Entrance

[0238] 18 Exit

[0239] 20, 20A, 20B flow path

[0240] 22 Entrance Correspondence

[0241] 24 Export Correspondence Department

[0242] 26 Crossroads

[0243] 28 Solid cement

[0244] 30 1st surface (surface)

[0245] 32 Surface 2

[0246] 34 No.1 solid adhesive

[0247] 36 2nd solid adhesive

[0248] 38, 38A welding part

[0249] 40 Entrance side inclined road

[0250] 42 Exit side inclined road

[0251] 44 Inclined part

[0252] 46 Length direction

[0253] 48 Bottom

Claims

1. A method for manufacturing a heat exchanger, comprising a pre-joining step and a joining step, In the pre-bonding step, a laminated body is prepared in which a surface sheet, a solid bonding agent, and a flow path forming sheet are sequentially arranged, the solid bonding agent mainly comprising at least one amorphous thermoplastic resin selected from thermoplastic epoxy resins and phenoxy resins, and the flow path forming sheet has a flow path on a surface opposite to the surface sheet. In the bonding step, the laminate is heated and pressurized to melt the solid bonding agent, thereby bonding the surface sheet and the flow path forming sheet. The epoxy equivalent of the amorphous thermoplastic resin is 1,600 or more, or the amorphous thermoplastic resin does not contain an epoxy group, and the heat of fusion of the amorphous thermoplastic resin is 15 J / g or less.

2. The method for manufacturing a heat exchanger according to claim 1, The heating and pressurizing are performed under the conditions of 100° C. to 400° C. and 0.01 MPa to 20 MPa.

3. The method for manufacturing a heat exchanger according to claim 1 or 2, The solid bonding agent before melting has any one shape selected from the group consisting of a film, a rod, particles, and a powder.

4. The method for manufacturing a heat exchanger according to claim 1 or 2, The surface sheet and the flow path forming sheet are made of metal.

5. A heat exchanger comprising a surface sheet, a flow path forming sheet, and an adhesive layer for bonding the surface sheet and the flow path forming sheet. The adhesive layer comprises a solid bonding agent having at least one amorphous thermoplastic resin selected from thermoplastic epoxy resins and phenoxy resins as a main component, The epoxy equivalent of the amorphous thermoplastic resin is 1,600 or more, or the amorphous thermoplastic resin does not contain an epoxy group, and the heat of fusion of the amorphous thermoplastic resin is 15 J / g or less.

6. The heat exchanger according to claim 5, The surface sheet and the flow path forming sheet are made of metal.

7. The heat exchanger according to claim 5 or 6, The surface sheet has an inlet and an outlet, The flow path forming sheet has a flow path on a surface opposite to the surface sheet. The flow path includes: an inlet corresponding portion connected to the inlet, an outlet corresponding portion connected to the outlet, and a plurality of intersections extending in a direction intersecting a direction connecting the inlet corresponding portion and the outlet corresponding portion. The surface sheet and the flow path forming sheet are joined to each other by welding so as to surround the outside of the flow path. The adhesive layer is provided at least at one location along the plurality of intersections.

8. The heat exchanger according to claim 7, The surface sheet comprises a first surface sheet and a second surface sheet, The flow path penetrates the flow path forming sheet in the thickness direction, The first surface sheet, the flow path forming sheet and the second surface sheet are sequentially provided in the thickness direction. The first surface sheet is provided with the inlet and the outlet.

9. The heat exchanger according to claim 7, The surface sheet comprises a first surface sheet and a second surface sheet, The flow path penetrates the flow path forming sheet in the thickness direction, The first surface sheet, the flow path forming sheet and the second surface sheet are sequentially provided in the thickness direction. The first surface sheet is provided with the inlet, and the second surface sheet is provided with the outlet.